Life satisfaction in older adults: associations with time perception and individual resources - Murciano Hueso, Alicia; Torrijos Fincias, Patricia; Martín García, Antonio Víctor (Revista Complutense de Educación, 2024)
INTRODUCTION. The concept of time is key to understanding how people age, playing an important role in the health and perceived well-being of older people. METHOD. This research aims to study the associations between the perception of future time, age, and satisfaction with the quality of life of older adults, taking individual resources (self-reported health conditions, cognitive capacity, and physical functions) as moderating factors. The study design is quantitative and non-experimental (ex post facto), using the questionnaire technique. The sample consisted of a total of 509 people over 60 years of age living in Spain. RESULTS. The results reveal that most of the sample presents an extended future time perspective, a perception that is associated with life satisfaction even after considering individual resources such as self-perceived health, and physical and cognitive functioning. Moreover, with increasing age, a more limited time perspective is associated with lower life satisfaction; (c) individual resources moderated these associations, especially self-reported health conditions. DISCUSSION. It is understood then that the way in which older people perceive future time turns out to be an indicator of satisfaction with their quality of life and well-being, independently of factors such as age or individual resources, which allows us to stress the importance of subjective time in relation to satisfactory adaptation in old age.
Keywords: ageing; quality of life; time; health; social welfare